Bienzymatic Acetylcholinesterase and Choline Oxidase Immobilized Biosensor Based on a Phenyl Carboxylic Acid-Grafted Multiwalled Carbon Nanotube - So-Ra Lee; Hyo-Eun Lee; Yun Ok Kang; Wan-Seok Hwang; Seong-Ho Choi (Advances in Materials Science and Engineering)
Bienzymatic acetylcholinesterase (AChE) and choline oxidase (ChOx) immobilized biosensor based on a phenyl carboxylic acid-grafted multiwalled carbon nanotube (MWNT) modified glass carbon electrode (GCE) and carbon-screen printed electrode (SPE) was fabricated for acetylcholine detection in human blood samples. Phenyl carboxylic acid-modified MWNT supports were prepared by electrochemical polymerization of 4-carboxyphenyl diazonium salts, which were synthesized by an amine group and sodium nitrite, on the surface of the MWNT-modified GCE and SPE in 0.1 M PBS. The successful fabrication of the AChE-ChOx-immobilized biosensor was confirmed via scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), electrochemical impedance spectroscopy (EIS), and cyclic voltammetry (CV). The sensing range of the biosensor based on a GCE and SPE was 1.0~10 μM and 10~100 μM, respectively. The interfering effect of 0.1 M L-ascorbic acid, 0.1 M L-cysteine, and 0.1 M uric acid to 0.1 M acetylcholine was 3.00%, 9.00%, and 3.00%, respectively. Acetylcholine in a human blood sample was detected by the AChE-ChOx-immobilized biosensor.